2018
DOI: 10.1111/myc.12848
|View full text |Cite
|
Sign up to set email alerts
|

A clarion call for preventing taxonomical errors of dermatophytes using the example of the novelTrichophyton mentagrophytesgenotype VIII uniformly isolated in the Indian epidemic of superficial dermatophytosis

Abstract: An alarming pan Indian increase in the incidence of superficial dermatophytosis has been noticed over the past 5-6 years. Recent studies have demonstrated emerging predominance of Trichophyton (T.) mentagrophytes as the causative organism in such cases. Interestingly, a distinct Indian genotype of T. mentagrophytes has been identified and recognised with the help of sequencing of the ITS region of the rDNA. That has, however, led to a basic confusion owing to the newly introduced taxonomy of dermatophytes in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
0
75

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(202 citation statements)
references
References 14 publications
3
124
0
75
Order By: Relevance
“…All of them belonged to Type VIII and harboured single‐point mutations in the squalene epoxidase ( SQLE ) gene . Singh et al reported a large series of 20 terbinafine resistant strains among 63 T mentagrophytes isolates that later were found to belong to genotype VIII by Nenoff et al The genotypic affiliation of remained 43 susceptible isolates remained obscure. Interestingly, all terbinafine resistant isolates in our study also had ITS region sequence Type VIII.…”
Section: Discussionmentioning
confidence: 99%
“…All of them belonged to Type VIII and harboured single‐point mutations in the squalene epoxidase ( SQLE ) gene . Singh et al reported a large series of 20 terbinafine resistant strains among 63 T mentagrophytes isolates that later were found to belong to genotype VIII by Nenoff et al The genotypic affiliation of remained 43 susceptible isolates remained obscure. Interestingly, all terbinafine resistant isolates in our study also had ITS region sequence Type VIII.…”
Section: Discussionmentioning
confidence: 99%
“…Im Gegensatz zu den veröffentlichten Fallstudien werden hier 37 Patienten beschrieben, die innerhalb von 18 Monaten die Klinik für Dermatologie an der Charité Berlin besuchten und Tinea-Infektionen, meist Tinea genitalis, aufwiesen, die durch den neuen Genotyp T. mentagrophytes , verursacht wurden. In Anlehnung an die von Heidemann et al 2010 [ 5 ] festgelegten und von Nenoff et al [ 19 ]…”
Section: Discussionunclassified
“…In contrast to the published case studies, we describe 37 patients who suffered from tinea infections (mostly tinea genitalis) caused by the new T. mentagrophytes genotype, and who visited the dermatological outpatient clinic within a period of 18 months. Following the nomenclature scheme established by Heidemann et al 2010 and grouped into a series of additional T. mentagrophytes variants by Nenoff et al , this genotype will be named T. mentagrophytes VII throughout the rest of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented low in vitro susceptibility towards fluconazole, itraconazole, ketoconazole, terbinafine, naftifine, griseofulvin and ciclopirox ; clinical isolates of T rubrum and T interdigitale that are resistant to allylamines, particularly terbinafine, with point mutations in the squalene epoxidase‐encoding gene, have also been reported . Owing to problems with molecular identification, the distinction between the anthropophilic T interdigitale and zoophilic T mentagrophytes leads to some taxonomical confusion …”
Section: Introductionmentioning
confidence: 99%